Importance of Small Forest Fragments in Agricultural Landscapes for Maintaining Orangutan Metapopulations - Ancrenaz, Marc; Oram, Felicity; Nardiyono, Nardiyono; Silmi, Muhammad; Jopony, Marcie E. M.; Voigt, Maria; Seaman, Dave J. I.; Sherman, Julie; Lackman, Isabelle; Traeholt, Carl; Wich, Serge A.; Santika, Truly; et al. (Frontiers in Forests and Global Change, 2021)
Historically, orangutans (Pongo spp.) lived in large contiguous areas of intact rainforest. Today, they are also found in highly modified and fragmented landscapes dominated by oil palm or industrial timber plantations; a situation that calls for new conservation approaches. Here we report signs of orangutan presence in more than 120 small forest fragments of less than 500 ha in size and isolated in extensive oil palm plantations across Borneo. We confirmed the long-term presence of adult resident females with dependent young in 42% of the fragments assessed by ground survey (n=50), and the regular sightings of males traveling across the landscape. We argue that orangutans using and living in small isolated forest patches play an essential part in the metapopulation by maintaining gene flow among larger sub-populations distributed across multiple-use landscapes. In some cases, translocations may be necessary when the animals are in imminent danger of being killed and have no other refuge. However, the impacts of removing animals from spatially dispersed metapopulations could inadvertently decrease critical metapopulation functionality necessary for long-term viability. It is clear that orangutans need natural forest to survive. However, our findings show that forest fragments within agricultural landscapes can also complement conservation areas if they are well distributed, properly connected and managed, and if orangutan killing is prevented. Efforts to better understand the dynamics and the functionality of an orangutan metapopulation in forest-farmland landscape mosaics characteristic of the Anthropocene are urgently needed to design more efficient conservation strategies for the species across its range.